RANCANGAN SISTEM PENGADAAN STOK BARANG PADA PT. LAJU KARUNIA JAYA - Erna Astriyani; Rahmadi Rahmadi; Ahmad Ricky Alfariz (UNIVERSITAS RAHARJA, 2017)
PT. The rate of gift Jaya is a company engaged in construction services and highway construction installation, As a service company certainly requires working in accordance with the operational procedures for settling an employment project. Part procurement very important role in supporting the implementation of the project work, are the shortcomings and constraints on systems running that application is still using semi computerized and manual where the goods into warehouse inputted from purchase orders into Microsoft Excel and the items will be out of the barn still applying registration manual with scrap paper, this led to weak control of the stocks held in warehouse which affect the shortages of goods and excess inventory, and often there is a discrepancy reporting items, Where complicate the process of procuring goods back to the warehouse. From the analysis that goes researchers used data collection methods and depiction poured using the Unified Modeling Language(UML). The results of this analysis are intended to develop a procurement system inventory based websites, which use as a data control goods in and goods out in the warehouse.